2019
DOI: 10.1021/acsomega.8b03490
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Quantum Dot-Anchored Bismuth Oxide Composites as Potential Electrode for Lithium-Ion Battery and Supercapacitor Applications

Abstract: The present investigation elucidates a simple hydrothermal method for preparing nanostructured bismuth oxide (Bi 2 O 3 ) and carbon quantum dot (CQD) composite using spoiled (denatured) milk-derived CQDs. The formation of the CQD–Bi 2 O 3 composite was confirmed by UV–vis absorption, steady-state emission, and time-resolved fluorescence spectroscopy studies. The crystal structure and chemical composition of the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 50 publications
1
58
0
Order By: Relevance
“…C-QDs have been combined with many supercapacitor electrode materials to enhance their performances by modifying either their electrochemical properties or their surface properties. C-QDs have been reported to provide carbon matrices to improve their electrical conductivity and solid electrolyte interface stability [ 145 ]. Wei et al reported that a combination of NaOH treatment and the addition of C-QDs into carbon matrices would give a large hierarchical structure which provides ion-buffering reservoirs resulting in better electronic properties.…”
Section: Recent Progress Of Carbon-based Qd Compositesmentioning
confidence: 99%
“…C-QDs have been combined with many supercapacitor electrode materials to enhance their performances by modifying either their electrochemical properties or their surface properties. C-QDs have been reported to provide carbon matrices to improve their electrical conductivity and solid electrolyte interface stability [ 145 ]. Wei et al reported that a combination of NaOH treatment and the addition of C-QDs into carbon matrices would give a large hierarchical structure which provides ion-buffering reservoirs resulting in better electronic properties.…”
Section: Recent Progress Of Carbon-based Qd Compositesmentioning
confidence: 99%
“…7b and listed in Table S5. BSH-1 provided an amazing energy density of 118 Wh kg -1 at the power density of 1.15 kW kg -1 , much higher than those of the reported symmetric device based on CQD-Bi 2 O 3 (88 Wh kg -1 ) 27 and asymmetric devices, such…”
Section: Resultsmentioning
confidence: 76%
“…The bad rate capability and low power density are mainly attributed to multielectron Faradic reactions of the unmatched Bi 2 O 3 electrodes for charge storage, which reflect relatively slower electrochemical kinetics than that of high-rate capacitive electrodes. To solve this, constructing composite structure has been considered as an effective strategy, resulting in the formation of Bi 2 O 3 /carbon composite electrodes, such as Bi 2 O 3 /activated carbon, 25,26 Bi 2 O 3 /carbon quantum dot, 27,28 Bi 2 O 3 /graphene. 28 For instance, a graphene/carbon dots encapsulation structure for the Bi 2 O 3 electrode supported by carbon nanotube films, has been reported to not only improve the conductivity but also inhibit the loss of capacity, which can account for the asymmetric supercapacitor with the energy density of 98.2 Wh kg -1 and the capacity retention of 80.1% after 8000 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Fang et al [113] prepared polypyrrole-coated Bi 2 O 3 @CMK-3 nanocomposite, which exhibited enhanced performance of lithium storage due to the synergetic effect of nanosize Bi 2 O 3 , conductive CMK-3 and PPy layer (Figure 8e). Prasath et al [114] fabricated a novel carbon quantum dot (CQD)-anchored Bi 2 O 3 composite used as anode materials for LIBs, delivering a discharge capacity high up to 1500 mAh g −1 at 0.2 C.…”
Section: Bismuth Oxidesmentioning
confidence: 99%
“…Prasath et al. [ 114 ] fabricated a novel carbon quantum dot (CQD)‐anchored Bi 2 O 3 composite used as anode materials for LIBs, delivering a discharge capacity high up to 1500 mAh g −1 at 0.2 C.…”
Section: Applications Of Bi‐based Materials In Libs/sibsmentioning
confidence: 99%